2020
DOI: 10.2147/idr.s264068
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Impacts of Deep Surgical Site Infections on Readmissions, Length of Stay, and Costs: A Matched Case–Control Study Conducted in an Academic Hospital in the Netherlands</p>

Abstract: Objective: This study aimed to evaluate the impacts of deep surgical site infections (dSSIs) regarding hospital readmissions, prolonged length of stay (LoS), and estimated costs. Patients and Methods: We designed and applied a matched case-control observational study using the electronic health records at the University Medical Center Groningen in the Netherlands. We compared patients with dSSI and non-SSI, matched on the basis of having similar procedures. A prevailing topology of surgeries categorized as cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…3 suggest that infectious complications could be driving readmissions. This is consistent with existing literature that reveals how SSI can lead to increased readmission rates, making it a potential target to improve quality measures [18,19]. Dirtier wound class was significantly associated with surgical site infections and sepsis, which may explain why wound class was significantly prognostic of readmission in this study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…3 suggest that infectious complications could be driving readmissions. This is consistent with existing literature that reveals how SSI can lead to increased readmission rates, making it a potential target to improve quality measures [18,19]. Dirtier wound class was significantly associated with surgical site infections and sepsis, which may explain why wound class was significantly prognostic of readmission in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Dirtier wound class was significantly associated with surgical site infections and sepsis, which may explain why wound class was significantly prognostic of readmission in this study. In a case control study, prophylactic antibiotics was found to be protective of deep SSI during initial surgical admission [ 18 ]. Optimization of antibiotic use or source control among “non-clean” surgeries should be investigated further to examine its effect on readmission rate.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical site infections are the most common and complex healthcare-associated infections. Surgical site infections could lead to patient mortality and increased cost of care (Bhangu et al, 2018 ; Purba et al, 2020 ; Silvestri et al, 2018 ). Although surgical site infections have declined in the past decade, their rate in China is still problematic, especially during operations.…”
Section: Introductionmentioning
confidence: 99%
“…Our results were also consistent with previous study which found that deep surgical site infections were associated with re-hospitalization, prolonged LoS and increased costs. 29 Furthermore, hospital re-admission is common in survivors of critical illnesses and increases stress on the patients and their caregivers. According to a previous systematic review and meta-analysis study, re-admission rates after critical illness were 16.9% (95%CI: 13.3-21.2%) within 30 days.…”
Section: A Comparative Effectiveness Study In Health Care Management ...mentioning
confidence: 99%